EU digital economy: features of formation and development prospects - Shirinova Shokhsanam Sobir kizi (Genius Journals, 2024)
The European Union (EU) has been at the forefront of the digital transformation, significantly reshaping its economic landscape. This article explores the key features and development prospects of the EU digital economy. Initially, it defines the concept and structure of the digital economy, highlighting its core components such as e-commerce, digital services, and information and communication technologies (ICT). The article addresses the importance of digital skills and education in preparing the workforce for a digital future, as well as the issue of digital inequality
Keywords: EU digital economy; Digital transformation; E-commerce